Epidemiology of Huntington's disease in Finland - Jussi O.T. Sipilä; Marja Hietala; Ari Siitonen; Markku Päivärinta; Kari Majamaa (Elsevier, 2022)
OBJECT:
To estimate the prevalence of Huntington's disease (HD) in Finland.
METHODS:
Persons diagnosed with HD from 1987 to 2010 were identified in the national registers and hospital records of the identified patients, and death certificates of the deceased subjects were obtained. Results of genetic analyses were obtained from the two national laboratories.
RESULTS:
Following the discovery of the Huntingtin gene (HTT), the rate of new diagnoses of HD has increased in Finland. We ascertained 207 patients with HD, 114 of whom were alive on 31 December, 2010 suggesting a minimum estimate of point prevalence of 2.12/100,000. The age at the time of diagnosis was 52.6 ± 12.1 years (mean ± standard deviation) and the duration of the disease was 8.5 ± 4.4 years among deceased patients. The length of the CAG repeats in the affected allele was 43.3 ± 3.5 repeats and the length was inversely correlated with the age at diagnosis (β = -0.73, p < 0.001). The number of diagnoses varied regionally, whereas the repeat length did not. The frequency of the high risk HTT haplogroup A was 39% in Finnish chromosomes abstracted from the 1000 Genomes database compared to 53% in other European samples (p = 0.024).
CONCLUSIONS:
The annual rate of HD diagnoses and the age at diagnosis have increased. The prevalence of HD in the Finnish population is lower than that of other Caucasian populations, partly explained by the low frequency of HTT haplogroup A among the Finns.